217k views
0 votes
Solve the equation, and check the solutions ∛(9-x)=6.

User EXODIA
by
5.0k points

1 Answer

3 votes

Answer:

The solution is:
x = -207

Explanation:

We have the following equation:


\sqrt[3]{9-x} = 6

Elevating both sides to 3, we can isolate x


\sqrt[3]{9-x}^(3) = 6^(3)


9-x = 216


-x = 216 - 9

Multiplying by -1


x = -207

Checking


\sqrt[3]{9-(-207)} = \sqrt[3]{216} = 6

User RomanHouse
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.